Tuberculosis among patients with unilateral pleural effusion in Kelantan: prevalence and associated factors - Rahman, Nor Haslina Abdul (2018)
Background Tuberculosis pleural effusion is a well-known aetiology among patient with unilateral pleural effusion. With the increasing prevalence of Extra-pulmonary TB in Malaysia and particularly in Kelantan state, many TB pleura cases still undiagnosed among this population. This can be due to lack of experience among the clinicians in identifying the potential risk factors for TB pleural effusion. Hence, the aims of this study are to determine the proportion of TB pleural effusion and the factors associated with it. Methodology This is a retrospective study which involved a total of 376 patients with unexplained unilateral pleural effusion who underwent medical thoracoscopy from 1st January 2011 until 31th December 2016 was identified from registration book in Respiratory Clinic, Hospital Raja Perempuan Zainab II. Relevant details on sociodemographic data (age, gender, race, smoking history, comorbidity, clinical presentation), laboratory pleural fluid analysis (protein, LDH, glucose, culture, AFB, MTB culture, TB PCR, Gene Xpert ) and thoracoscopy findings ( nodule, mass, adhesion, plaque, sago-like lesion and cheesy-like lesion) were collected from the medical review. Multiple logistic regression were used to analyses the data. Results The proportion of TB pleura amongst unexplained unilateral pleural effusion were 38.3%. Lung malignancy contribute the highest proportion in 44.4% followed by para pneumonic effusion in 10.1% and chronic kidney disease in 2.7%. Based on multiple logistic regression analyses, sago-like lesion is the strongest determinant factors associated with TB pleura (OR 37.41 (CI: 7.81, 179.24), p value = < 0.001) and cheesy-like lesion (OR 30.44 (CI 12.73, 72.80), p value = < 0.001). The present of past history of pulmonary TB is also associated with TB pleura (OR 9.23(CI 1.95, 43.67), p value = 0.005) and fever (OR 4.70 (CI 2.21, 9.97), p value = <0.001). In addition to that, MTB culture is also the strongest determinant for TB pleura with (OR 6.80 (CI 2.16, 21.45), p value 0.001) and TB PCR with (OR 8.71 (CI 2.54, 29.94), p value 0.001). The presence of a mass from thoracoscopy is less likely associated with TB pleura (OR 0.13 (CI 0.02, 0.70), p value 0.018). Conclusion Past history of Pulmonary TB, fever, positive MTB culture and positive TB PCR and demonstration of cheesy-like and sago-like lesion from thoracoscopy are strongly associated with TB pleura. Knowing these significant factors will help the clinicians to diagnose TB pleura so that treatment can be start earlier to avoid morbidity and mortality.